Bilateral vocal cord palsy causing stridor as the only symptom of syringomyelia and Chiari I malformation, a case report. (2016) - Yousif, Saif; Walsh, Mark; Burns, Hannah
Highlights: We present the case of a three year old female who had a long standing stridor, previously being incorrectly managed as asthma by family practitioner. She was found to have a bilateral vocal cord palsy causing her stridor, as a result of a large syrinx formation and Arnold Chiari malformation. We highlight the importance of MRI as a diagnostic tool in the evaluation of vocal cord palsy and stridor. Abstract: Introduction: Bilateral vocal cord palsy is a condition which has many causes (Gupta et al., 2012)[1] . Syringomyelia is an uncommon condition which describes the formation of fluid filled cavity, occupying the spinal cord (Chang, 2003)[2] . It rarely manifests itself as subacute onset of stridor. Presentation of case: We present the case of a three year old female who presented for evaluation of her speech and language delay, when incidentally it was made note of her loud breathing which had previously been managed as bronchiolitis by her general practitioner. In hospital she was found to have a bilateral vocal cord palsy. Further investigation revealed a large syrinx as well as an associated Arnold Chiari 1 malformation, for which she required neurosurgical decompression. Conclusion: Although uncommon, formation of a syrinx should be considered for patients who present with stridor and reiterates the importance of MRI as an important investigative tool of bilateral vocal cord palsy.